A laminate assembly interconnection structure and manufacturing method thereof
By using solder paste with low melting point, using alloy components such as indium tin silver, tin bismuth, tin silver, etc., for interval coating or screen printing, the problems of high welding temperature and high conductive adhesive cost in the prior art are solved. , realizes cell electrode interconnection under low temperature conditions, increases flexibility and reduces thermal stress, and improves the reliability and competitiveness of the components.
Patent Information
- Application Number
- CN201910726951.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-08-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2039-08-07
AI Technical Summary
In the interconnection materials between cell electrodes, the welding tape has a high welding temperature and is harmful to the environment, the conductive adhesive is costly and has a high thermal stress, which reduces the reliability of the battery.
Use low melting point solder paste to coat or screen printing through alloy components such as indium tin silver, tin bismuth, tin silver or indium tin alloy to realize the partition connection of battery electrodes, increase flexibility and reduce heat. stress.
The interconnection of battery electrodes is achieved under low temperature conditions, increasing the flexibility of the battery string after lamination, reducing thermal stress, reducing production costs, and improving the reliability and competitiveness of components.
Smart Images

Figure CN110429153B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell assembly packaging, manufacturing and application, and in particular to a laminate assembly interconnection structure and a manufacturing method thereof. Background Art
[0002] With the accelerated consumption of conventional fossil energy such as coal, oil, and natural gas, the ecological environment is deteriorating, and the greenhouse gas emissions are leading to increasingly severe global climate change. The sustainable development of human society has been seriously threatened. Considering the limited stock of non-renewable energy and the serious environmental pollution caused by conventional fossil energy, countries around the world have formulated their own energy development strategies to cope with the limited resources of conventional fossil energy and the environmental problems caused by its development and utilization. Under this world trend, solar energy has become one of the most important renewable energy sources with its reliability, safety, extensiveness, longevity, environmental protection, and sufficient resources, and is expected to become the main pillar of global electricity supply in the future.
[0003] In the context of vigorously promoting and using solar green energy, researchers have found that stacking module technology can significantly increase module power. Stacking technology uses special graphic design to re-cut the entire solar cell into small graphics, and then use conductive glue to glue together several adjacent cells with good efficiency and appearance consistency or directly physically bond them through the carrier transmission channel on the surface of the cell to manufacture a module. Stacking technology can reduce module loss and increase module output power by optimizing the module structure and reducing interconnection strips.
[0004] The current mainstream process of stacked components uses conductive adhesives to interconnect the cut cells. The conductive adhesive is mainly composed of a conductive phase and a bonding phase and completes the current transmission between the interconnected cells. The conductive phase is mainly composed of precious metals, such as pure silver particles or silver-coated copper, silver-coated nickel, silver-coated glass and other particles. The shape and distribution of the particles are based on the optimal electrical conduction. At present, most of the silver powders with a D50<10um grade are in the form of flakes or spherical combinations. The bonding phase is mainly composed of weather-resistant polymer resins. Acrylic resins, silicone resins, epoxy resins, polyurethanes, etc. are usually selected according to bonding strength and weathering stability. In order to achieve low contact resistance, low volume resistivity, high bonding and maintain long-term excellent weathering properties, general conductive adhesive manufacturers will complete the design of the conductive phase and bonding phase formula to ensure the stability of the performance of the stacked components in the initial environmental corrosion test and long-term outdoor actual application. Compared with conventional alloy interconnected components, stacked components have fewer years of actual large-scale application and are currently a new type of component product. The reliability of the product itself can only be verified after long-term comprehensive outdoor aging.
[0005] At present, the conductive materials between the electrodes of the battery cells in the stacked assembly include conductive adhesive, solder strips or solder paste and other materials. Among them, the solder strips are mainly tin-lead solder strips, which have high welding temperatures and are harmful to the environment, and are prone to cause hidden cracks and fragments in the battery cells; the conductive adhesive is mainly composed of a conductive phase and an adhesive phase, wherein the adhesive phase is mainly composed of a weather-resistant polymer resin polymer, and acrylic resin, silicone resin, epoxy resin, polyurethane, etc. are usually selected according to the bonding strength and weathering stability. The conductive phase is mainly composed of precious metals, such as pure silver particles or silver-coated copper, silver-coated nickel, silver-coated glass and other particles. However, since silver is a precious metal, the cost of conductive adhesive is very expensive, and traditional solder paste requires high welding temperatures, poor toughness, and large thermal stress, which reduces the reliability of the battery. Summary of the invention
[0006] The object of the present invention is to provide a laminate assembly interconnection structure and a manufacturing method thereof to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A laminated component interconnection structure, comprising a shingled sheet, wherein a front electrode is printed on the front side of the sheet, and a back electrode is printed on the back side of the sheet, wherein the front electrode of the shingled sheet is connected to the back electrode of an adjacent shingled sheet by solder paste, wherein the solder paste is applied or printed between the front electrode and the back electrode in an interval manner, and the melting point of the solder paste is less than 160°;
[0009] The solder paste is an indium tin silver alloy, which is composed of three alloy elements: indium, tin and silver. The indium content accounts for 40-60% of the total mass of indium tin silver, the tin content accounts for 40-60% of the total mass of indium tin silver, and the silver content accounts for 0.5-3.9% of the total mass of indium tin silver.
[0010] Preferably, the solder paste replaces the indium-tin-silver alloy with a tin-bismuth alloy, wherein the tin content accounts for 40-42% of the total mass of the tin and bismuth, and the bismuth content accounts for 58-59% of the total mass of the tin and bismuth.
[0011] Preferably, the solder paste replaces the indium tin silver alloy with a tin-silver alloy, wherein the tin content accounts for 96-97% of the total mass of the tin-silver, and the silver content accounts for 3-4% of the total mass of the tin-silver.
[0012] Preferably, the solder paste replaces the indium tin silver alloy with an indium tin alloy, wherein the indium content accounts for 52-54% of the total mass of the indium tin, and the tin content accounts for 45-48% of the total mass of the indium tin.
[0013] Preferably, the solder paste is formed by combining any two or more of indium tin silver, tin bismuth, tin silver or indium tin.
[0014] Preferably, the cross-section of the solder paste is set to be elliptical, trapezoidal or square.
[0015] A method for manufacturing a laminate assembly comprises the following steps:
[0016] S1. Screen printing is performed on the battery cell produced through the normal process, and a plurality of front electrodes and front grid lines are printed on the front side of the battery cell, and a plurality of back electrodes are printed on the back side of the battery cell;
[0017] S2. After the front and back printing is completed by screen printing, the printed pattern is ensured to ensure that the front electrode and the back electrode of each shingled piece are printed at the staggered positions of the front and back respectively after the cell is cut;
[0018] S3. Use intermittent quantitative coating or screen printing to connect the front and back electrodes of the shingled pieces in different areas through solder paste to achieve interconnection and stringing of the shingled pieces.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The low-melting-point solder paste designed by the present invention interconnects the electrodes of the battery cells under low-temperature conditions, and designs the shapes of different welding points at the same time, thereby increasing the flexibility of the battery string after lamination and reducing thermal stress. The low-melting-point solder paste of high-conductivity solder alloy is used, and the solder paste is applied by screen printing or quantitative coating to realize alloying interconnection between small pieces in different regions, thereby enhancing the reliability of the components. The solder paste is made of one or more alloy components of indium tin silver, tin bismuth, tin silver or indium tin. The unique composition ratio makes the production cost of the solder paste lower than that of the conductive glue containing the precious metal silver, thereby greatly reducing the production cost and improving the product competitiveness of the enterprise. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the interconnection structure of the present invention;
[0022] Figure 2 It is a schematic diagram of interconnection of shingled components of the present invention;
[0023] Figure 3 It is a schematic diagram of the back structure of the shingled sheet of the present invention.
[0024] In the figure: 1. shingled piece, 2. front side of piece, 3. front side electrode, 4. solder paste, 5. back side of piece, 6. back side electrode. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] See also Figure 1-3 , the present invention provides a technical solution:
[0027] A laminated component interconnection structure comprises a plurality of shingled sheets 1 obtained by cutting, a front surface 2 of the shingled sheet 1 is printed with a front electrode 3 and a front gate line, and a back surface 5 of the shingled sheet 1 is printed with a back electrode 6, as shown in the attached manual Figure 2 As shown, the front electrode 3 of each shingled sheet 1 is connected to the back electrode 6 of another adjacent shingled sheet 1 through solder paste 4. The solder paste 4 is applied or printed between the front electrode 3 and the back electrode 6 in an interval manner. It is designed according to discontinuous low stress. The solder paste 4 can be applied or printed on the front electrode 3 or the back electrode 6. The cross-section of the solder paste 4 is set to an elliptical, trapezoidal or square shape. The elliptical setting makes the solder paste 4 in the contact and interconnection process of the two shingled sheets 1. Compared with the setting of the commonly used solder paste, the elliptical interconnection effect of the present application is better. The melting point of the solder paste 4 is less than 160°. The use of low-melting-point solder paste 4 to interconnect the electrodes of the battery cells under low temperature conditions can increase the flexibility of the battery string after lamination and reduce thermal stress.
[0028] The solder paste 4 is composed of one or more of indium tin silver, tin bismuth, tin silver or indium tin.
[0029] Embodiment 1: The solder paste 4 is an indium tin silver alloy, which is composed of three alloy elements: indium, tin and silver, wherein the indium content accounts for 50% of the total mass of indium tin silver, the tin content accounts for 48% of the total mass of indium tin silver, and the silver content accounts for 2% of the total mass of indium tin silver.
[0030] Example 1-1: The solder paste 4 is an indium tin silver alloy, which is composed of three alloy elements: indium, tin and silver, wherein the indium content accounts for 40% of the total mass of indium tin silver, the tin content accounts for 59% of the total mass of indium tin silver, and the silver content accounts for 1% of the total mass of indium tin silver.
[0031] Example 1-2: The solder paste 4 is an indium tin silver alloy, which is composed of three alloy elements: indium, tin and silver, wherein the indium content accounts for 58% of the total mass of indium tin silver, the tin content accounts for 40.5% of the total mass of indium tin silver, and the silver content accounts for 1.5% of the total mass of indium tin silver.
[0032] Embodiment 2: The solder paste 4 is a tin-bismuth alloy, which is composed of tin and bismuth alloy elements, wherein the tin content accounts for 42% of the total mass of the tin and bismuth, and the bismuth content accounts for 58% of the total mass of the tin and bismuth.
[0033] Embodiment 3: The solder paste 4 is made of tin-silver alloy, which is composed of tin and silver alloy elements, wherein the tin content accounts for 96.5% of the total mass of tin-silver, and the silver content accounts for 3.5% of the total mass of tin-silver.
[0034] Embodiment 4: The solder paste 4 replaces the indium-tin-silver alloy with an indium-tin alloy, wherein the indium content accounts for 52% of the total mass of the indium-tin, and the tin content accounts for 48% of the total mass of the indium-tin.
[0035] Embodiment 5: The solder paste 4 is a combination of indium tin silver alloy and tin bismuth alloy, wherein the indium tin silver alloy is an alloy with the same proportion as in Embodiment 1, and the tin bismuth alloy is an alloy with the same proportion as in Embodiment 2, and the indium tin silver alloy and the tin bismuth alloy each account for 50% of the total mass.
[0036] Example 6: Solder paste 4 is a combination of indium tin silver alloy, tin silver alloy and indium tin alloy, wherein the indium tin silver alloy is an alloy with the same ratio in Example 1, the tin silver alloy is an alloy with the same ratio in Example 3, and the indium tin alloy is an alloy with the same ratio in Example 4, the indium tin silver alloy accounts for 50% of the total mass, and the tin silver alloy and the indium tin alloy each account for 25% of the total mass.
[0037] After being manufactured, the solder paste 4 in the above-mentioned embodiments 1 to 6 can well increase the flexibility of the battery string after lamination and enhance the reliability of the assembly.
[0038] The following steps are required to manufacture a laminate assembly with the above interconnection structure, that is, a method for manufacturing a laminate assembly:
[0039] S1. Use single crystal silicon wafers to obtain a good textured surface structure through surface texturing, thereby increasing the specific surface area to receive more photons and reducing the reflection of incident light;
[0040] S2. Clean the residual liquid during the texturing process to reduce the influence of acidic and alkaline substances on the battery formation;
[0041] S3, phosphorus atoms are obtained by reacting phosphorus oxychloride with silicon wafers. After a certain period of time, the phosphorus atoms enter the surface layer of the silicon wafer and diffuse into the interior of the silicon wafer through the gaps between silicon atoms, forming an interface between N-type semiconductor and P-type semiconductor, completing the diffusion bonding process and realizing the conversion of light energy into electrical energy;
[0042] S4. Since the diffusion junction forms a short-circuit channel at the edge of the silicon wafer, the photogenerated electrons collected on the front of the PN junction will flow along the edge where phosphorus is diffused to the back of the PN junction, causing a short circuit. The edge PN junction is etched away by plasma etching to avoid short circuits at the edge, which can increase the SE process steps.
[0043] S5. Since the diffusion bonding process will form a layer of phosphorus-silicate glass on the surface of the silicon wafer, the effect on the efficiency of the shingled cell can be reduced by removing the phosphorus-silicate glass.
[0044] S6. The etched silicon wafer is then placed in an oxygen high temperature furnace at a certain temperature to produce a layer of silicon dioxide on the front and back sides of the cell;
[0045] S7, then depositing a layer of aluminum oxide passivation film by ALD or PECVD;
[0046] S8, depositing a silicon nitride film layer on the aluminum oxide passivation film layer, wherein the front silicon nitride film layer is used to reduce reflection and passivation, and the back silicon nitride film layer is used to protect the aluminum oxide passivation film layer;
[0047] S9, laser grooving the back side of the coated silicon wafer;
[0048] S10, completing the back and front printing by screen printing, so that the front electrode 3 and the back electrode 6 of the shingled sheet 1 after the printed pattern is cut are printed at the staggered positions of the front and back, and then performing a sintering process;
[0049] S11. Reduce the light-induced degradation of the battery by using a light decay furnace or an electric injection furnace;
[0050] S12, finally, perform battery test and grading;
[0051] S13. For the sintered whole shingled cell, an online laser cutting and scribing process is added. The sintered shingled cell enters the scribing inspection position for appearance inspection and visual positioning of the OK cell. According to the online production rhythm, the multi-track scribing machine or the preset cache stack area can be freely set to realize online continuous feeding operation. According to the optimal effect of cutting and scribing, the laser related parameters are set to achieve faster cutting speed, narrower cutting heat affected zone and cutting line width, better uniformity and predetermined cutting depth. After the automatic cutting is completed, the automatic breaking mechanism of the online laser scribing machine is used to complete the splitting at the cutting position to realize the natural separation of the shingled small cell, and the cutting is completed;
[0052] Among them, the laser cutting surface is far away from the PN junction side to avoid damage to the PN junction and leakage current. It is necessary to confirm the front and back directions of the battery cell before dicing and loading. If the direction is opposite, a separate 180° reversing device needs to be added;
[0053] S14, connecting the front electrode 3 and the back electrode 6 of the shingled sheet 1 in different regions by means of interval quantitative coating or screen printing through the solder paste 4;
[0054] S15, then interconnect the shingled pieces 1 into strings and alloy them in a curing furnace or a hot plate;
[0055] S16. After the strings are made, the shingled photovoltaic modules are packaged through the following steps: automatic string layout and convergence, film and backboard laying, mid-term inspection, lamination, trimming, framing, middle junction box, curing, cleaning, and testing.
[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A laminated component interconnection structure, comprising a shingled sheet (1), wherein a front electrode (3) is printed on a front side (2) of the shingled sheet (1), and a back electrode (6) is printed on a back side (5) of the shingled sheet (1), characterized in that: The front electrode (3) of a shingled sheet (1) is connected to the back electrode (6) of an adjacent shingled sheet (1) via solder paste (4), wherein the solder paste (4) is applied or printed between the front electrode (3) and the back electrode (6) in an interval manner, and the melting point of the solder paste (4) is less than 160°; The solder paste (4) is an indium tin silver alloy, which is composed of three alloy elements: indium, tin and silver, wherein the indium content accounts for 40-60% of the total mass of the indium tin silver, the tin content accounts for 40-60% of the total mass of the indium tin silver, and the silver content accounts for 0.5-3.9% of the total mass of the indium tin silver.
2. The interconnection structure of a laminate assembly according to claim 1, characterized in that: In the indium tin silver alloy, the indium content accounts for 50% of the total mass of the indium tin silver, the tin content accounts for 48% of the total mass of the indium tin silver, and the silver content accounts for 2% of the total mass of the indium tin silver.
3. The interconnection structure of a laminate assembly according to claim 1, characterized in that: In the indium tin silver alloy, the indium content accounts for 40% of the total mass of the indium tin silver, the tin content accounts for 59% of the total mass of the indium tin silver, and the silver content accounts for 1% of the total mass of the indium tin silver.
4. The interconnection structure of a laminate assembly according to claim 1, characterized in that: In the indium tin silver alloy, the indium content accounts for 58% of the total mass of the indium tin silver, the tin content accounts for 40.5% of the total mass of the indium tin silver, and the silver content accounts for 1.5% of the total mass of the indium tin silver.
5. The interconnection structure of a laminate assembly according to claim 1, characterized in that: The cross section of the solder paste (4) is configured to be elliptical, trapezoidal or square.
6. A method for manufacturing a lamination assembly, characterized in that: The lamination assembly comprises the lamination assembly interconnection structure according to any one of claims 1 to 5, and the manufacturing method comprises the following steps: S1, screen printing is performed on the battery cell produced through the normal process, a plurality of front electrodes (3) and front grid lines are printed on the front side of the battery cell, and a plurality of back electrodes (6) are printed on the back side of the battery cell; S2, after the front and back surfaces are printed by screen printing, the printed pattern is ensured to ensure that the front electrode (3) and the back electrode (6) of each shingled sheet (1) are printed at staggered positions on the front and back surfaces respectively after the cell is cut; S3, using a method of intermittent quantitative coating or screen printing, the front electrode (3) and the back electrode (6) of the shingled pieces (1) are connected in different areas through solder paste (4), so as to realize interconnection and stringing of the shingled pieces (1).
Citation Information
Patent Citations
A method for improving photoelectric conversion efficiency of battery sheet
CN109192792A
Electrode wire for solar cell, its base material, and manufacturing method of base material
JP2009016593A
Method for manufacturing solar cell module and solar cell module
JP2014229754A
KR1018740160000B1